2000
DOI: 10.3109/02770900009055432
|View full text |Cite
|
Sign up to set email alerts
|

The Allocation of Family Responsibility for Asthma Management Tasks in African-American Adolescents

Abstract: The allocation of responsibilities for asthma management within African-American families was examined in 60 adolescents and their primary caretakers. Separate structured interviews were conducted with adolescents and primary caretakers, and perceptions of family management, adherence to asthma treatment regimen, and functional morbidity were assessed. Support for the primary hypothesis that higher levels of nonadherence and functional morbidity would be observed in families where caretakers overestimated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 22 publications
3
58
0
Order By: Relevance
“…Several studies have found that, for children with chronic illness, discrepancies in parent and child reports of decision making autonomy specifically regarding the management of the child's medical regimen (i.e. whether the child or parent is responsible for daily illness management tasks) may be related to higher family conflict, nonadherence, and morbidity (Miller & Drotar, 2003;Walders, Drotar, & Kercsmar, 2000). Further research on the nature of discrepancies between family members' reports of trajectory of autonomy development in children with spina bifida may provide a greater understanding of family relationship transformations that may occur over time.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that, for children with chronic illness, discrepancies in parent and child reports of decision making autonomy specifically regarding the management of the child's medical regimen (i.e. whether the child or parent is responsible for daily illness management tasks) may be related to higher family conflict, nonadherence, and morbidity (Miller & Drotar, 2003;Walders, Drotar, & Kercsmar, 2000). Further research on the nature of discrepancies between family members' reports of trajectory of autonomy development in children with spina bifida may provide a greater understanding of family relationship transformations that may occur over time.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found limited variability in responses to most items, suggesting that a different response set may improve the measure. A similar measure to assess responsibility for asthma management has the respondent rate each task on a 5-point Likert-type scale ranging from 1 (parent is completely responsible) to 5 (child is completely responsible), 12 although only limited support was found for the relationship between that measure and children's adherence. 12,72 Another option would have respondents report how frequently over a set period of time a caregiver (versus child) actually completed each task.…”
Section: Family Experiences With Antiretroviral Therapymentioning
confidence: 99%
“…Research among adolescents with a variety of chronic illnesses suggests that children assume increasing levels of responsibility for disease management as they mature, [8][9][10][11] and at least one study suggests that caregivers may assume less responsibility as children become older. 12 At the same time, adherence problems increase as children get older, [13][14][15] especially during adolescence. [15][16][17][18] Thus, children and adolescents may be given responsibility for regimen-related tasks when they may be unlikely to complete them successfully.…”
mentioning
confidence: 99%
“…Fourth, roles for managing asthma may not be clearly defined. Caretakers may not adequately assess or monitor the child's asthma management abilities (22,23) or negotiate developmentally appropriate responsibilities for asthma management tasks among caregivers and children (24,25).…”
mentioning
confidence: 99%